2020
DOI: 10.3390/jcm9092776
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Plasma-Polymerized Allylamine Coating of Zirconia after Five Years

Abstract: Plasma-polymerized allylamine (PPAAm) coatings of titanium enhance the cell behavior of osteoblasts. The purpose of the present study was to evaluate a PPAAm nanolayer on zirconia after a storage period of 5 years. Zirconia specimens were directly coated with PPAAm (ZA0) or stored in aseptic packages at room temperature for 5 years (ZA5). Uncoated zirconia specimens (Zmt) and the micro-structured endosseous surface of a zirconia implant (Z14) served as controls. The elemental compositions of the PPAAm coatings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…After extensive long-term research, zirconia has been confirmed to be suitable for application in dental implants ( Kunrath et al, 2021 ). A number of surface modification methods have been attempted to enhance the bioactivity of zirconia implants ( Rohr et al, 2020 ). In this study, pre-sintered zirconia was subjected to water bath treatment and dense sintering to obtain TiO 2 -coated modified zirconia.…”
Section: Discussionmentioning
confidence: 99%
“…After extensive long-term research, zirconia has been confirmed to be suitable for application in dental implants ( Kunrath et al, 2021 ). A number of surface modification methods have been attempted to enhance the bioactivity of zirconia implants ( Rohr et al, 2020 ). In this study, pre-sintered zirconia was subjected to water bath treatment and dense sintering to obtain TiO 2 -coated modified zirconia.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma polymerized coating could be durable and resistant towards ageing [24], oxidation, and shrinking [25]. It is noteworthy to mention that, the long-term ultraviolet radiation, oxygen oxidation, and dust accumulation reduces the effect of plasma treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 5 shows the diameter distribution of the PAl particles synthesized at different power, approximately 770 particles were measured in each case. The graphs were made with a normal distribution function, see Equation (1), where f(ϕ) is the normal distribution function, ϕ is particle diameter, μ is harmonic mean, and ρ is standard deviation. 18 The harmonic mean is the maximum value in each distribution.…”
Section: Morphologymentioning
confidence: 99%
“…In terms of properties, PAl synthesized by plasma has shown biocompatibility with different human body systems. [1][2][3] Particularly, PAl particles are being studied as implants in the central nervous system to reconnect the neuronal communication after a severe lesion. 4 However, PAl is usually obtained as films.…”
Section: Introductionmentioning
confidence: 99%